Partial migration and early size of southern hake Merluccius australis: a journey between estuarine and oceanic habitats off Northwest Patagonia. (6th December 2018) - Toledo, Pamela; Darnaude, Audrey M; Niklitschek, Edwin J; Ojeda, Vilma; Voué, Raphaël; Leiva, Félix P; Labonne, Maylis; Canales-Aguirre, Cristian B
Abstract: Partial migration is a key adaptive strategy, increasingly observed across multiple taxa. To investigate partial migration and life-cycle diversity of Merluccius australis in northwestern Patagonia, we analysed isotopic (δ 13 C, δ 18 O) and elemental ( 11 B, 23 Na, 24  Mg, 55 Mn, 86 Sr, 138 Ba) compositions of otoliths from juveniles, sub-adults, and adults to identify nursery origins, habitats used, and migratory behaviours of multiple cohorts (1990–2005). Influence of early size upon migration was assessed by comparing back-calculated sizes at demersal recruitment between resident and migratory adults. Although partial migration occurred at both estuarine and oceanic nursery habitats, migratory behaviour was more frequent in fish of estuarine origin (59%) than in fish of oceanic origin (17%). Adults of estuarine origin dominated both estuarine (92%) and oceanic (77%) sampling areas. Although we found no significant differences in size at demersal recruitment between oceanic-resident and oceanic-migratory fish, a strong relationship between size at demersal recruitment and migratory behaviour appeared in fish of estuarine origin, whose probability of migration increased from 5% to 95% as demersal recruitment size increased from 18.8 to 23.6 cm. Further research on M. australis life cycle is required to incorporate sub-population processes into the stock assessment and management models being used for this overexploited species.